The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23137488
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-Mediated Adipogenesis in Different Adipocytes

Abstract: Long-chain noncoding RNAs (lncRNAs) are RNAs that do not code for proteins, widely present in eukaryotes. They regulate gene expression at multiple levels through different mechanisms at epigenetic, transcription, translation, and the maturation of mRNA transcripts or regulation of the chromatin structure, and compete with microRNAs for binding to endogenous RNA. Adipose tissue is a large and endocrine-rich functional tissue in mammals. Excessive accumulation of white adipose tissue in mammals can cause metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 154 publications
(158 reference statements)
0
9
0
Order By: Relevance
“…It is critical to study the biological function of adipocytes in food-producing animals. Recently, lncRNAs have emerged as crucial regulators that regulate lipid accumulation or white fat browning in adipocytes in multiple ways. , Using RNA-seq, Yang et al found 501 DE-lncRNAs at different differentiation stages (0, 3, 6, and 9 d) of bovine intramuscular preadipocytes . Li et al identified 16 differentially expressed lncRNAs related to the late stage of adipocyte differentiation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical to study the biological function of adipocytes in food-producing animals. Recently, lncRNAs have emerged as crucial regulators that regulate lipid accumulation or white fat browning in adipocytes in multiple ways. , Using RNA-seq, Yang et al found 501 DE-lncRNAs at different differentiation stages (0, 3, 6, and 9 d) of bovine intramuscular preadipocytes . Li et al identified 16 differentially expressed lncRNAs related to the late stage of adipocyte differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…adipocytes in food-producing animals. Recently, lncRNAs have emerged as crucial regulators that regulate lipid accumulation or white fat browning in adipocytes in multiple ways 29,30. Using RNA-seq, Yang et al found 501 DE-lncRNAs at different differentiation stages (0, 3, 6, and 9 d) of bovine intramuscular preadipocytes 31.…”
mentioning
confidence: 99%
“…Many lncRNAs associated with adipogenesis have recently been reported in animals, playing a crucial role in animal fat deposition. 32,33 In plants, lncRNA has been reported to be involved in oil synthesis in B. napus, O. sativa, Paeonia suffruticosa, and J. curcas. Here, the lncRNA43234 gene was screened from the lncRNA−miRNA−mRNA coexpression network based on pretranscriptome sequencing.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Many lncRNAs associated with adipogenesis have recently been reported in animals, playing a crucial role in animal fat deposition. , In plants, lncRNA has been reported to be involved in oil synthesis in B. napus, O.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have revealed that lncRNAs can interact with protein‐coding genes and regulate them by directly competing with the binding of microRNAs and therefore participate as competing endogenous RNAs in the regulation of fundamental cellular processes (Xu et al., 2022; Zhao et al., 2023). Moreover, a plethora of evidence suggests the contribution of lncRNAs in the regulation of metabolism and fat deposition (Lu et al., 2021; Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%